2016
DOI: 10.1371/journal.pone.0160906
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Activity in Geriatric Rehabilitation: A Randomized Controlled Trial of Accelerometry

Abstract: BackgroundLow activity levels in inpatient rehabilitation are associated with adverse outcomes. The study aimed to test whether activity levels can be increased by the provision of monitored activity data to patients and clinicians in the context of explicit goal setting.MethodsA randomized controlled trial in three sites in Australia included 255 inpatients aged 60 and older who had a rehabilitation goal to become ambulant. The primary outcome was patients’ walking time measured by accelerometers during the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(94 citation statements)
references
References 39 publications
1
93
0
Order By: Relevance
“…Our findings are in line with previous studies [8,15,16,18,19] although the observed effects varied and outcomes were limited to walking duration and up-time. Two studies in different disease groups were performed from 2008-2010 in the same geriatric hospital as the present study with a similar design but a much smaller sample size and a different sensor system [15,16].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are in line with previous studies [8,15,16,18,19] although the observed effects varied and outcomes were limited to walking duration and up-time. Two studies in different disease groups were performed from 2008-2010 in the same geriatric hospital as the present study with a similar design but a much smaller sample size and a different sensor system [15,16].…”
Section: Discussionsupporting
confidence: 92%
“…Three studies used the same sensor system as in the current study, two of them evaluated daily walking duration [8,18] and one study used upright duration as the outcome measure [19]. The results were inconsistent, reflecting much smaller sample sizes, different study designs and settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are hypothetical reasons why inpatient rehabilitation may not be beneficial, or even harmful, for some patients. It is recognised that patients in rehabilitation wards are generally inactive for most of the day and that the ward environment facilitates rest in bed. The amount of therapy promoting mobility provided each day is limited.…”
mentioning
confidence: 99%